Comparison of adverse effects in the treatment of pulmonary hypertension with monotherapy and combination therapy - Anam, Ahmed Nazmul; Hossain, Nazmul; Jahan, Hasrat; Podder, Bidhan Chandra; Karim, Monzurul (International Journal of Research in Medical Sciences, 2022)
Background: Pulmonary arterial hypertension (PAH) is a serious condition characterized by an increase in pulmonary vascular resistance (PVR) that leads to right heart failure and death. The study aimed to compare the side effects of monotherapy and combination therapy in the treatment of pulmonary hypertension Methods: This randomized control trial study was conducted at the department of pediatric cardiology, Bangabandhu Sheikh Mujib medical university, national institute of cardiovascular disease, and national heart foundation, Dhaka, Bangladesh. The study duration was 1 year, from January 2018 to December 2018. During this period, a total of 70 participants were selected for the study following the inclusion, and exclusion criteria from those diagnosed case of pulmonary hypertension with congenital heart disease admitted to the pediatric cardiology department, Bangabandhu Sheikh Mujib medical university, NICVD, NHF. Result: Maximum patients had ventricular septal defects (VSD) (34.3% in group A, and 28.6% in group B). Followed by AVSD. 20.0% in group A and 25.7% in group B. Atrial septal defect (ASD) were 14.3% in group A, and 17.1% in group B. After three, and 6 months of follow-up SpO2 per exercise, 6MWD, SpO2 post-exercise, and alanine aminotransferase showed statistically significant differences between single and combined groups. There was no statistically significant difference regarding adverse effects between the 2 groups, but group B patients had slightly higher incidence of some side effects. PASP was significantly decreased in combined group than monotherapy group. Conclusions: This study concludes that combination therapy is more successful than monotherapy in PAH with coronary heart disease (CHD). Our findings demonstrate that combining Bosentan with oral Sildenafil medication in patients with CHD-related PAH is safe, and well tolerated at 3-, and 6-month follow-ups, resulting in a significant improvement in clinical status, effort SpO2, exercise tolerance, hemodynamics, and PASP.